2020
DOI: 10.3390/ani10112029
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Improvements in Zoo-Housed Elephant Welfare: A Case Study at ZSL Whipsnade Zoo

Abstract: Over the last two decades, criticisms were raised regarding the welfare experienced by elephants in European and North American zoos. Concerns regarding the welfare of zoo-housed elephants in the UK and Europe were consolidated in the publication of several key reports, and media interest peaked. Throughout this study we aim to outline the behavioural measures of welfare observed in the current group of Asian elephants (Elephas maximus) at Zoological Society of London (ZSL) Whipsnade Zoo, using key welfare ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 59 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…While improvements in animal welfare provisioning over the last half‐century within most accredited ‘western' zoos, and likely many more besides would be hard to dispute (see Kitchener & MacDonald, 2002; Finch et al, 2020; Tidière et al, 2016), these improvements have likely at best, kept pace with a growing awareness of, and concern for animal welfare among the general populace (see Marinova & Fox, 2019; Robbins et al, 2018; L. E. Webb et al, 2019). Furthermore, it is also likely that zoos and aquariums have made more fundamental improvements in the provisioning of physical wellbeing than they have in delivering psychological wellbeing (Veasey, 2017) with most species now living longer in zoos than they would in the wild (see Tidière et al, 2016), but with stereotypies and other abnormal behaviours still being routine for many species (see Clubb & Mason, 2003, 2007; Mason & Veasey, 2009a, 2009b, 2010; Swaisgood & Shepherdson, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While improvements in animal welfare provisioning over the last half‐century within most accredited ‘western' zoos, and likely many more besides would be hard to dispute (see Kitchener & MacDonald, 2002; Finch et al, 2020; Tidière et al, 2016), these improvements have likely at best, kept pace with a growing awareness of, and concern for animal welfare among the general populace (see Marinova & Fox, 2019; Robbins et al, 2018; L. E. Webb et al, 2019). Furthermore, it is also likely that zoos and aquariums have made more fundamental improvements in the provisioning of physical wellbeing than they have in delivering psychological wellbeing (Veasey, 2017) with most species now living longer in zoos than they would in the wild (see Tidière et al, 2016), but with stereotypies and other abnormal behaviours still being routine for many species (see Clubb & Mason, 2003, 2007; Mason & Veasey, 2009a, 2009b, 2010; Swaisgood & Shepherdson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…While improvements in animal welfare provisioning over the last half-century within most accredited 'western' zoos, and likely many more besides would be hard to dispute (see Kitchener & MacDonald, 2002;Finch et al, 2020;Tidière et al, 2016), these improvements have likely at best, kept pace with a growing awareness of, and concern for animal welfare among the general populace (see Marinova & Fox, 2019;Robbins et al, 2018;L. E. Webb et al, 2019).…”
Section: Animal Welfare As An Opportunity Rather Than a Costmentioning
confidence: 99%
“…Studies on the behavior of zoo-housed animals are typically limited to zoos' opening hours of operation (i.e., during the day), which consequently limits our knowledge of these animals and how they behave throughout the entire 24 h period [18]. Remote monitoring over 24 h periods can provide valuable insights about how zoo-housed animals behave [24,25], which can guide decisions that enhance their welfare. Remote monitoring during this study revealed at least three individual penguins swam overnight between the hours of 0:00-6:00.…”
Section: Discussionmentioning
confidence: 99%
“…Emitting a low frequency rumble call An ethogram (12,16) was used when assessing the daytime activity of the elephants. They were directly observed for three consecutive days from 08:00 h to 16:00 h. This time was divided into four intervals: 8:00-10:00 h, 10:00-12:00 h, 12:00-14:00 h, and 14:00-16:00 h. In each of these four intervals, the elephants were observed for a minimum of 5 minutes for their daytime activity.…”
Section: Rumblementioning
confidence: 99%